2019
DOI: 10.1038/s41467-019-12322-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of marine sediment diagenesis in the modern oceanic magnesium cycle

Abstract: The oceanic magnesium cycle is largely controlled by continental weathering and marine authigenic mineral formation, which are intimately linked to long-term climate. Uncertainties in the magnesium cycle propagate into other chemical budgets, and into interpretations of paleo-oceanographic reconstructions of seawater δ26Mg and Mg/Ca ratios. Here, we produce a detailed global map of the flux of dissolved magnesium from the ocean into deeper marine sediments (greater than ∼1 meter below seafloor), and quantify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Our simulated diagenesis experiments suggest that, similar to today (Berg et al 2019;Sun et al 2016), a sink for magnesium in Archean time may have been in the Mg enrichment of silicates during sedimentary diagenesis and burial. For example, studies of the Amazon delta sediments have shown that Mg is incorporated in secondary silicate clays during simulated and observed diagenesis (Michalopoulos and Aller 1995;Rude and Aller, 1989).…”
Section: Effects Of Simulated Diagenesis On Fe(iiiii) Silicatesmentioning
confidence: 68%
“…Our simulated diagenesis experiments suggest that, similar to today (Berg et al 2019;Sun et al 2016), a sink for magnesium in Archean time may have been in the Mg enrichment of silicates during sedimentary diagenesis and burial. For example, studies of the Amazon delta sediments have shown that Mg is incorporated in secondary silicate clays during simulated and observed diagenesis (Michalopoulos and Aller 1995;Rude and Aller, 1989).…”
Section: Effects Of Simulated Diagenesis On Fe(iiiii) Silicatesmentioning
confidence: 68%
“…A marine origin is supported by high Mg-concentrations of the calcite (4300 ± 1700 ppm, Suppl. Data 1), as high Mg is characteristic for abiotic marine carbonates (e.g., Berg et al, 2019). There are also very high Fe concentrations in the calcites (18,000 ± 5000 ppm, Suppl.…”
Section: Fossil Record In Igneous Oceanic Crustmentioning
confidence: 94%
“…Previous estimates for global carbonate authigenesis were based primarily on the Ca 2+ flux into sediments from the overlying water column and do not account for Ca 2+ fluxes toward shallow sediment from deep methanogenic zones due to MSiW (Longman et al, 2019). Further, a higher authigenic carbonate sink is expected when Mg 2+ fluxes into shallow marine sediments are also considered along with the Ca 2+ fluxes (Berg, 2018;Berg et al, 2019). Moreover, the CH 4 and SO 4 2− flux data used in this study from the compilation by Egger et al (2018) covers a higher number of diffusive methane flux locations from IODP and non-IODP AOM and OSR consumes 70% and 30% of SO 4 2− entering the SMTZ, respectively, F (DIC-deep) = 50% of CH 4 flux, F carb = 20%, F SOC = 5%, and F (DIC-out) = 75% of the Total (DIC) .…”
Section: Importance Of Methane Derived Authigenic Carbonate Precipitamentioning
confidence: 99%